Trading Zones im Kloster: Controlling in der Sozialwirtschaft - Ingo Husmann (IU Internationale Hochschule, 2021)
– Business management concepts and especially controlling are of fundamental importance for the survival of social economy enterprises. Nevertheless, controlling in the social economy is often met with resistance or even rejection. The reasons for this lie above all in an institutional conflict between the number-oriented economic efficiency logic of controlling and the logic of accepted efficiency renunciation in the social economy. This paper therefore asks how business management controlling can be made fruitful in the social economy. To investigate the phenomenon of controlling in the social economy, the present study refers to the concept of trading zones. The empirical data was collected in a single case study in a Christian monastery. The research results confirm both the need for controlling in the social economy, but also its institutional rejection. Based on the concept of trading zones, this study shows concrete possibilities for overcoming this institutional conflict to make controlling fruitful in the social economy. As a first conceptualization and empirical analysis of the trading zone concept in the context of controlling in the social economy, this paper advances the current understanding of controlling in social economy enterprises.
urn:nbn:de:101:1-2021121709131357101873
Keywords: M21; 650; Controlling; Nonprofit Organisationen; Sozialwirtschaft; Trading Zones; Organizational Institutional Logics